Resolving Institutional Dualism of Election Supervisory Institutions in Aceh Province: Penyelesaian Dualisme Kelembagaan Lembaga Pengawas Pemilihan Umum di Provinsi Aceh - Fahmi, Khairul; Putra, Ilhamdi; Arrasuli, Beni Kharisma (Jurnal Konstitusi, 2024)
Until now, the institutional dualism of election monitoring institutions and regional elections in Aceh still exists. This condition still leaves problems in the implementation of election supervision and regional elections in Aceh. This article focuses discussion on aspects of legal policy choices that can be taken to resolve this dualism. This research is normative legal research which fully uses secondary data in the form of primary and secondary legal materials. This study concludes that the root of the problem of dualism in the election and regional election supervisory institutions in Aceh is due to the lack of synchronization in the regulation of the Election Law and the Regional Election Law with the Aceh Government Law. This was also reinforced by the Constitutional Court's decision which stated that Article 557 and Article 571 letter d of the Election Law were contrary to the UUD 1945 because their formation was not in accordance with the provisions of the amendment to the Aceh Government Law contained in the Aceh Government Law itself. This research recommends that the institutional dualism of election and regional election supervisory institutions in Aceh be ended immediately by making changes to the Election Law, Regional Election Law and Aceh Government Law.